Pelatihan Pembuatan Telur Asin Dalam Rangka Menigkatkan UMKM Desa Babo Kecamatan Bandar Pusaka Aceh Tamiang - Ibnu Abdillah; Nuryufa Maura; Rizka Amelia; Ahmad Fuadi; Enni Suhenni (peduli riset dan pengabdian masyarakat, 2024)
Salted egg is a snack food that is quite popular among various groups. These eggs can be obtained at food stalls,traditional markets, supermarkets, and hawkers. However, the quality of salted eggs circulating in the markettoday is generally very concerning. It is estimated that only about 10% of the salted eggs in the market today areof good quality. Cooked salted eggs packed with three eggs and sold at the most expensive supermarket outlets arenot fit to eat, the egg whites are damaged. While salted eggs sold at food stalls, the egg whites are brownishbecause they use saltpeter preservatives (potassium nitrate (KNO3)). Good quality salted eggs are currently veryrare in the market. A salted egg entrepreneur who maintains quality, usually always has difficulty serving ordersdue to limited production capabilities. The egg salting process takes about two weeks (15 days). This time is longenough to fulfill the needs. Materials for salting eggs are quite a lot of quantities and requirements to producegood quality salted eggs. The purpose of the study was to determine the effect of various salted egg making mediaon organoleptic quality so that it becomes a material consideration and information in the use of the right saltedegg making media and get better quality. In the implementation of this study, the experimental design used was aCompletely Randomized Design (CRD), with 3 treatments and 5 replications. Treatments: PG; Salt solution,PA; Rubbing ash dough and PL; clay / clay dough. While the organoleptic test of salted eggs consisting of; 1. 2.Salty taste of egg white and 3. The taste of egg yolk. The data obtained were analyzed descriptively and Kruskall-Walis non-parametric model. The results showed that the treatment had a significant effect on the generalappearance of the egg, the salty taste of egg white and the masir taste of egg yolk, the PG treatment (salt solution)showed the same thing as the PA treatment (rubbed ash dough) but different from the PL treatment (clay dough).